Damped Algorithms for the Split Fixed Point and Equilibrium Problems - Li-Jun Zhu; Minglun Ren (Journal of Function Spaces and Applications)
The main purpose of this paper is to study the split fixed point and equilibrium problems which includes fixed point problems, equilibrium problems, and variational inequality problems as special cases. A damped algorithm is presented for solving this split common problem. Strong convergence analysis is shown.